Asaia accelerates larval development of Anopheles gambiae. (1st September 2013) - Mitraka, Elvira; Stathopoulos, Stavros; Siden-Kiamos, Inga; Christophides, George K; Louis, Christos
Abstract : Arthropod borne diseases cause significant human morbidity and mortality and, therefore, efficient measures to control transmission of the disease agents would have great impact on human health. One strategy to achieve this goal is based on the manipulation of bacterial symbionts of vectors. Bacteria of the Gram-negative, acetic acid bacterium genus Asaia have been found to be stably associated with larvae and adults of the Southeast Asian malaria vector Anopheles stephensi, dominating the microbiota of the mosquito. We show here that after the infection of Anopheles gambiae larvae with Asaia the bacteria were stably associated with the mosquitoes, becoming part of the microflora of the midgut and remaining there for the duration of the life cycle. Moreover they were passed on to the next generation through vertical transmission. Additionally, we show that there is an increase in the developmental rate when additional bacteria are introduced into the organism which leads us to the conclusion that Asaia plays a yet undetermined crucial role during the larval stages. Our microarray analysis showed that the larval genes that are mostly affected are involved in cuticle formation, and include mainly members of the CPR gene family.